GRACE score in assessing the risk of hospital outcomes in patients with pulmonary embolism - I. S. Mullova; N. A. Cherepanova; T. V. Pavlova; S. M. Khokhlunov; D. A. Gnilomedova; A. A. Leksina; D. V. Duplyakov (Российский кардиологический журнал)
Aim. To compare the PESI and GRACE scores in assessing the risk of hospital outcomes in patients with pulmonary embolism.Material and methods. The study included 383 patients with pulmonary embolism (PE), hospitalized during the period of April 4, 2003 on September 18, 2014; 190 (49,6%) are men, the average age is 57,4 years±14,4 years. We considered the patient’s anamnesis, complaints, results of biochemical and instrumental tests, as well as the treatment carried out to the patients.Results. According to the risk stratification of PESI score, 86 (22,5%) patients had a very low risk of death, 88 (22,9%) had a low risk, 94 (24,5%) had an intermediate risk, 60 (15,%) — high risk and 55 (14,4%) patients have a very high risk. The combination of three ECG signs (SI-QIII, right bundle branch block and T-wave inversion in V1-V3) was significantly more common in patients with a very high PE risk — 14,5% (p=0,025). The most reliable sign of the most echographic (echoCG) criteria was dilatation of right ventricle (RV) (p=0,009) in a group of patients with a very high PE risk. According to the GRACE scale, 112 (29,2%) patients were assigned to the low risk group, and 271 (70,8%) patients — to the high risk group. ECG signs were observed more frequently in the high risk group: SI-QIII, T-wave inversion in III, V1-V3 leads, right bundle branch block (p<0,05). Pulmonary hypertension and RV dilatation according to echoCG prevailed in the high risk group (98,4% and 85,1%, respectively), p<0,05. The minimum value of points on the GRACE score for the deceased patients was 118 points. The GRACE scale showed high predictive ability with a sensitivity of 96% and a specificity of 63% (AUC=0,811, CI 95% 0,0738-0,884). However, the PESI score had a slightly greater predictive value with a sensitivity of 100% and a specificity of 53% (AUC=0,879 compared with AUC=0,811 for the GRACE scale). Analysis of the PESI and GRACE scores showed a moderate correlation between them (r=0,668).Conclusion. The GRACE score showed a high predictive value for adverse outcomes in PE patients with a sensitivity of 96% and a specificity of 63%. The minimum score on the GRACE score for deceased patients was 118 points.